Performance Analysis of Specialty Fiber Optic Cables for Distributed Acoustic Sensing - Uyar, Faruk; Kartaloǧlu, Tolga; Erol, Mustafa; Özbay, Ekmel; Ozdur, Ibrahim T. (Optica Publishing Group (Formerly OSA), 2020)
In this work, we present the signal-to-noise ratio comparison results of six different buried fiber optic cable for identical external perturbations using a home-made direct detection φ-OTDR system. © 2023 Elsevier B.V., All rights reserved.
Keywords: Cables; Fiber Optics; Acoustic Sensing; Comparison Result; Direct-Detection; External Perturbations; Fiberoptic Cables; Fibre-Optic Cables; Performances Analysis; Specialty Fiber; Signal to Noise Ratio